CALON GURU PAUD DAN TANTANGAN MASA DEPAN: TEMUAN AWAL PANDANGAN MAHASISWA TENTANG PENDIDIKAN ABAD 21 - Ali Formen (Jurnal Ilmiah Visi, 2022)
Many have argued that early childhood education (ECE) is an investment for a better future. This claim perhaps is valid only if today’s ECE corresponds with the imagined future. Among the images of the future our education system promotes are the so-called 21st-century skills and their prerequisites, 21st-century education/learning. To further unpack today's ECE link with the intended future, this article presents dataset on ECE teacher candidates’ views about 21st-century skills, education, and learning. Sixty-one students of a Central Java-based university voluntarily participated in the study. Through an online questionnaire, they reported their knowledge about 21st-century education and readiness to become a 21st-century teacher. Nevertheless, their responses seem to disconnect from the literature on 21st-century education. Although not generalizable, these findings are critical for ensuring today’s teacher training alignment with the idea of ECE as an investment for a better future.